Job requirements, resources and proactive behavior at work: The role of work engagement and stress - Miselytė, Marija; Bagdžiūnienė, Dalia; Jakutė, Violeta (Psichologija, 2019)
Proactive employees are an important part of social capital in modern organizations that operate in a competitive and ever-changing business environment. Proactive behavior (PB) is defined as self-directed and future-oriented actions that are aimed to change the situation, work environment, or oneself (Bindl & Parker, 2010). Proactive workers initiate individual and organizational changes, and they not only respond to work requirements or adapt to environmental conditions (Fritz & Sonnentag, 2009). Therefore, it is important to analyze the work and personal characteristics that may be significant in order to enhance the employees’ PB. The paper presents an empirical study that integrates the theoretical approaches of Proactive Behavior (Parker & Collins, 2010) and Job Demands – Resources (Schaufeli & Bakker, 2004). It is aimed, first, to examine the links between job demands (pace and amount of work, emotional and mental workload), resources (autonomy and feedback), and work engagement and stress with employee strategic proactive behaviors as well as work and person-environment fit proactive behaviors. Second, to determine the role that work engagement and stress have in the relationships between job characteristics and PB types. A total of 386 employees from various Lithuanian organizations were surveyed online. Sixty one percent of the respondents were female; the average age of the respondents was 34.8 (SD = 11.32) years, with an average of 7.3 (SD = 8.22) years of working experience in their organizations. Twenty one percent of the respondents were first-level managers. Most of the respondents (93.6%) had acquired higher education. Structural equation modeling analyses revealed that strategic PB, through engagement as a mediator, was predicted by autonomy, mental workload, and feedback; proactive work behavior was predicted by emotional workload, while mental workload, autonomy, and feedback were related to proactive work behavior through work engagement as a mediator; proactive person-environment fit behavior was predicted only by feedback via work engagement as a mediator. The study has shown that employee PB can be reinforced not only with job resources (autonomy and feedback) but job demands as well (the mental and emotional workload) via the mediative effect of work engagement. Work stress was not related with PB. The practical applications of research findings are discussed.